BIOLOGICAL PROPERTIES OF THE SARS-COV-2 VIRUS ISOLATED FROM A DOG ON THE TERRITORY OF THE REPUBLIC OF KAZAKHSTAN - Sadikalieva , S.O.; Shayakhmetov, E.A.; Abay , Zh.S.; Nurpeisova , A.S.; Shoraуeva K.A.; Omurtaу A.D.; Kopeev , S.K.; Nakhanov , A.K.; Terebay , A.A.; Myrzakhmetova , B.Sh.; Kozhabergenov , N.S.; Abduraimov , Ye.O. (Eurasian Journal of Applied Biotechnology, 2023)
This article examined biological samples (28 swabs) taken from dogs in the Almaty region of the Republic of Kazakhstan as part of monitoring studies of the SARS-COV-2 virus among domestic animals. The resulting samples were analyzed by real-time RT-PCR, where seven (7) samples were detected within cycles 25-37. Further, these samples were cultured in Vero cell culture to determine the presence of the virus. As a result of reproduction on a Vero cell culture, a viral suspension of one isolate was obtained with the biological activity of 5.83±0.08 lgTCID50/cm3. In addition, Electron microscopy confirmed virion morphology similar to that of the Coronaviridae family. The data obtained indicate that pets can also get infected with COVID-19 coronavirus infection and be carriers of this disease.